Perancangan SOP Pengendalian Internal Pada PT.Gading Abadi Semesta - Yandi Suprapto; Angeline Aurellia (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
Internal company control is very necessary in every company so that its management can be better. This community service activity (PKM) carried out at PT Gading Abadi Semesta aims to realize better company management and management by implementing internal control SOPs. The methods used were observation, interviews, and documentation so that the results obtained were carried out by socializing the implementation of SOPs to employees. The conclusion regarding the output achieved in community service activities (PKM) is that standard operating procedures (SOP) for cash disbursements and cash receipts are created, so that every cash receipt and disbursement is recorded clearly and archived properly. And the existence of standard operating procedures (SOP) for product inventory makes stock recording much neater than before and with minimal shortages. The implementation process is carried out and followed by employees in accordance with the rules and regulations written in the Standard Operating Procedure (SOP).